39P TCR engaging antigen-scaffolds for targeted expansion of functionally improved T cells for adoptive cell therapy. (15th December 2019) - Kladis, G; Mindahl, V Rafa; Tamhane, T; Bentzen, A Kai; Donia, M; Svane, I M; Niessner, H; Sinnberg, T; Garbe, C; Jacobsen, S Nyboe; Schmees, C; Hadrup, S Reker
Abstract: Background: Precise targeting of patient's tumor can be facilitated through T cells recognizing specific pMHC complexes on these tumors. Once such antigen landscape is defined, an additional challenge relates to the ability to mount a functional T cell response specific to such antigens. Current T Cell expansion techniques provide no efficient strategy for antigen-specific stimulation and results largely in exhausted T cells. Here we present a new technology for ex-vivo peptide-MHC directed expansion and functional enhancement of T cells, using artificial antigen-presenting scaffolds (Ag-scaffolds). Methods: Dextran backbone conjugated with streptavidin was used for Ag-scaffold assembly. Such backbone was incubated together with biotinylated MHC class I molecules holding a given peptide (pMHC) and biotinylated human cytokines in various ratios. PBMCs from healthy donors with known virus epitopes and from melanoma patients with known epitopes were expanded for 2 weeks with Ag-scaffold, added when the cell cultures were initiated and twice per week for two weeks. The expansion of antigen-specific CD8 T cells was monitored and analyzed by flow cytometry. Results: Here we demonstrate the value of the antigen-scaffold based expansion, by the expansion of virus-CD8 T cells from peripheral blood, and tumor-specific T cells from both peripheral blood and tumor site. We can favorably expand both neo- and shared antigen specific T cell populations. The resulting T cell product exhibit a multifunctional cytokine profile upon antigen challenge, high levels of CD28 expression, and reduced levels of PD-1 expression. Importantly, numerous different pMHC-specific T-cell populations can be stimulated in a single culture, and we can obtain better tumor killing properties than conventional TIL-ACT products. Conclusion: This study presents a new technology for expanding functionally enhanced antigen-specific CD8 T cells suited for implementation to ACT strategies. T cell phenotype and functionality are known to be important parameters in successful adoptive T cell transfer, and hence it´s plausible that antigen scaffold based expanded T cell product may improve treatment outcome compared to conventional expansion strategies. Legal entity responsible for the study: The authors. Funding: Innovation Fund Denmark. Disclosure: All authors have declared no conflicts of interest.